Infrastructure, Governance, and Poverty Alleviation in Forest Conservation Zones - Mardiansyah, Ardi; Pitoyo, Agus Joko; Ikhwan, Hakimul; Kutanegara, Pande Made (Journal of Posthumanism, 2025)
This article examines the intersection of infrastructure, governance, and poverty alleviation in ecologically protected areas, focusing on Kampar Kiri Hulu in the Wildlife Reserve of Bukit Rimbang Bukit Baling (WR-BRBB), Riau Province, Indonesia. Despite national poverty reduction agendas, forest-edge communities face persistent multidimensional poverty driven by spatial isolation, legal constraints, and institutional fragmentation. Using policy ethnography, spatial mapping, and interviews, the study reveals that infrastructural exclusion is not merely a technical issue but rooted in rigid regulatory frameworks that prioritize conservation over basic services. It highlights the tension between environmental protection and development, documenting community adaptations such as gotong royong, adat-based governance, and small-scale eco-tourism or micro-hydro projects. The findings expose a governance paradox: conservation laws preserve ecosystems while simultaneously marginalizing residents and constraining local government action. The study proposes integrated policy responses, including collaborative governance (penta-helix), adaptive social protection, legal recognition of customary land, and investment in ecologically sensitive infrastructure. These recommendations aim to realign conservation with inclusive development. By grounding its analysis in the Kampar case, the article offers critical insights for addressing poverty in conservation zones across the Global South through socially embedded and territorially nuanced governance innovations.